Carotid plaque in STEMI: evidence of a missed opportunity to reclassify risk. (26th April 2021) - Croissant, Y; Costa, D; Gonzalez, C; Perea, C; Corsico, L; Acosta, F; Muzzio, M; Coronel, R
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: The presence of carotid plaque has been associated with an increased risk for acute coronary events, and can be assessed with a low-cost and readily available study such as carotid ultrasound. This has a class IIa recommendation to reclassify patients with intermediate risk, but little is known about the prevalence of carotid disease in patients with acute coronary syndromes. Methods: Observational study in patients admitted for STEMI in a tertiary care center, performing a carotid ultrasound before hospital discharge. We analyzed the differential characteristics according to the presence of carotid plaque, as well as the atherosclerotic burden assessed by the number of diseased vessels. Results: We included 191 patients with STEMI, and 57 (29.8%) had carotid plaque. Their basal characteristics and outcomes are listed in the table. Patients with subclinical atherosclerotic disease were older, but other risk markers were similar, as was the use of aspirin and statins. The prevalence of carotid disease increased with the number of diseased vessels, as seen in the figure. Conclusion: About 1 in 3 patients with STEMI had carotid plaque detectable by ultrasound. Most were young with an intermediate basal risk for cardiovascular disease, with only a minority treated with statins or aspirin, and could have been reclassified as high risk with a timely ultrasound. No other risk factors but age was associated with the presence of carotid plaque, emphasizing the importance of carotid ultrasound screening in older patients.